2022
DOI: 10.3390/ijms232113267
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Human Microbiome in the Pathogenesis of Pain

Abstract: Understanding of the gut microbiome’s role in human physiology developed rapidly in recent years. Moreover, any alteration of this microenvironment could lead to a pathophysiological reaction of numerous organs. It results from the bidirectional communication of the gastrointestinal tract with the central nervous system, called the gut–brain axis. The signals in the gut–brain axis are mediated by immunological, hormonal, and neural pathways. However, it is also influenced by microorganisms in the gut. The dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 171 publications
0
34
0
1
Order By: Relevance
“…An accumulating body of evidence has highlighted the existence of bidirectional interplay between the microbiome and CNS, and this interaction [ 3 ], the so-called gut–brain axis, has an impact on mood change [ 3 , 4 , 5 ], sleep disorders [ 6 ] and cognitive impairment [ 7 ], which are commonly reported in patients with FMS. In addition, recent studies have revealed that the composition of the gut microbiome can play a role in the central sensitization of chronic pain by regulating astrocytes, microglia, and other immune cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…An accumulating body of evidence has highlighted the existence of bidirectional interplay between the microbiome and CNS, and this interaction [ 3 ], the so-called gut–brain axis, has an impact on mood change [ 3 , 4 , 5 ], sleep disorders [ 6 ] and cognitive impairment [ 7 ], which are commonly reported in patients with FMS. In addition, recent studies have revealed that the composition of the gut microbiome can play a role in the central sensitization of chronic pain by regulating astrocytes, microglia, and other immune cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen has been reported to stimulate neural growth and differentiation both in vitro ( 63 ) and in animal studies ( 64 ). The gut-brain axis promotes the central sensitization of chronic pain ( 65 ). Therefore, endometriosis-associated pain may be affected by regulation of microglia and astrocytes via the dysbiotic gut-brain axis ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…The gut-brain axis promotes the central sensitization of chronic pain ( 65 ). Therefore, endometriosis-associated pain may be affected by regulation of microglia and astrocytes via the dysbiotic gut-brain axis ( 65 ). Severe pain and infertility associated with endometriosis have been reported to be associated with decreased cervical microbial diversity and abundance ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, T reg lymphocytes alleviate chronic neuropathic pain by inhibiting the Th1 response via CD4+ helper cells 42 . Emerging clinical evidence proposes that the pathogenesis of neuropathic pain may be a centrally-mediated neuroimmune phenomenon with an important contribution by the gut microbiome 43 , e.g. by influencing the balance between pro-inflammatory and anti-inflammatory T cells 44 .…”
Section: Discussionmentioning
confidence: 99%